2022
DOI: 10.3390/ijms232415927
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Preeclampsia In Vitro: Polymorphic Variants of STOX1-A/B Genes Can Downregulate CD24 in Trophoblast Cell Lines

Abstract: CD24 is a mucin-like immunosuppressing glycoprotein whose levels increase during pregnancy and decrease in the syncytio- and cytotrophoblasts in early and preterm preeclampsia. We used two modified cell lines that mimic in vitro features of preeclampsia to identify if this phenomenon could be reproduced. Our model was the immortalized placental-derived BeWo and JEG-3 cell lines that overexpress the STOX1 A/B transcription factor gene that was discovered in familial forms of preeclampsia. BeWo and JEG-3 cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Pancreatic cancer patients who received combined PARP1 and CD24 inhibition experienced a synergistic antitumor effect [ 47 ]. Polymorphic STOX1-A/B gene variations can suppress CD24 in trophoblast cell lines, according to an in vitro investigation that modeled preeclampsia [ 48 ].…”
Section: Cd24/siglec-10: Structures Expression Function and The Signa...mentioning
confidence: 99%
“…Pancreatic cancer patients who received combined PARP1 and CD24 inhibition experienced a synergistic antitumor effect [ 47 ]. Polymorphic STOX1-A/B gene variations can suppress CD24 in trophoblast cell lines, according to an in vitro investigation that modeled preeclampsia [ 48 ].…”
Section: Cd24/siglec-10: Structures Expression Function and The Signa...mentioning
confidence: 99%
“…Finally, Sammar et al [ 19 ] showed on in vitro models of preeclampsia that the overexpression of STOX1-A/B transcription gene, discovered in familial forms of preeclampsia, leads to the decreased expression of CD24, a mucin-like immunosuppressing glycoprotein, which was observed in syncytiothrophoblasts and cytotrophoblasts in early and preterm preeclampsia.…”
mentioning
confidence: 99%